The impact of stress on quality of life in female infertility patients with polycystic ovary syndrome - Le, Thi Thuan My; Nguyen, Thi Cuc; Le, Minh Tam (Tạp chí Y Dược Huế, 2024)
Objectives: Women with polycystic ovary syndrome (PCOS) are not only at high risk of reproductive, metabolic or physical health problems, but also easily suffer from psychological disorders such as stress, depression, anxiety, this has been proven to lower quality of life. Determining the negative effects of stress in infertile women with PCOS on quality of life is important and practically significant. This study aims to: (1) Describe stress levels and quality of life in female infertility patients with PCOS. (2) Identify some factors affecting quality of life in infertile women with PCOS. Materials and Methods: A cross-sectional study on 210 female infertile patients diagnosed with Polycystic Ovary Syndrome (PCOS) based on Rotterdam criteria Holland 2003 who came for examination and treatment at Hue Center for Reproductive Endocrinology and Infertility (HueCREI), Hue University of Medicine and Pharmacy hospital from May 2023 to May 2024. The DASS-21 scale (Depression Anxiety Stress-21) and the MPCOSQ one (the modified PCOS health-related QoL questionnaire) were used to survey the patient’s stress level and quality of life, respectively. The correlation between stress levels and patients’ quality of life scores was analyzed using the Pearson correlation coefficient (r). Comparing factors in terms of the diagnostic criteria for PCOS, other elements with quality of life, then finding relationships and making discussion. Results: In total of 210 patients recruited in this study, there were 75 patients suffering stress at different levels from mild, moderate to severe and highly severe, accounting for 21.0%, 10.5%, 3.3% and 1%, respectively. The average mPCOSQ score in terms of infertility factor was the lowest, at 3.71 ± 1.31 points. The study found a strong negative correlation between the average score of stress level based on the DASS-21 and the average score of quality of life based on the mPCOSQ (r= -0.861, p<0.001). What is more, the quality of life score in terms of infertility illness was the lowest, regardless of stress level (p<0.001). Furthermore, factors such as income level, BMI, acne and hirsutism have a statistically significant association with the quality of life of female infertile patients with PCOS (p<0.05). Conclusion: Stress has taken a toll on the quality of life in infertile women with PCOS. Particularly, of six domains related to the quality of life in female infertile patients with PCOS, infertility problems were obtained the lowest score no matter what stress level they are. On top of that, income, BMI and other factors such as acne, hirsutism can have a significant implication of the quality of life in infertile PCOS female patients.